PROBLEMATISASI PENERAPAN SISTEM RESTORATIVE JUSTICE TERHADAP PECANDU NARKOTIKA : ANTARA NARASI HUKUM DAN REALITAS PRAKTIK - Ngakan Putu Yudi Kusuma Putra; Indah Sari (YAYASAN PENDIDIKAN DAN PELAYANAN KESEHATAN RAHMAT HUSADA, 2025)
The handling of drug abuse cases in Indonesia faces a dilemma between conventional penal approaches and more humane rehabilitation efforts. Through the Restorative Justice framework, Indonesia’s legal system seeks not only to punish but also to restore drug users' conditions so they may reintegrate into society. This article employs normative legal research with a statute approach to evaluate the effectiveness of narcotics rehabilitation policy within Indonesia’s criminal justice system. The findings reveal a significant gap between progressive regulations and practical implementation, marked by low rehabilitation performance, weak inter-agency coordination, and insufficient understanding of restorative principles among law enforcers. The case study of the Surabaya District Attorney’s Office provides concrete evidence of substantive justice in action, though it remains sporadic. Therefore, a systemic synergy and institutional courage are needed to normalize this approach in national legal policy.